(untitled) (Indian Journal of Animal Production and Management, 2017)
A field survey was carried out in Gummidipoondi block of Thiruvallur district in Tamil Nadu during the years 2017-2018 among 120 farmers to assess the watering practices for livestock. The objective of this survey was to study the water sources available, contaminating sources of water, location of water trough, type of waterers, method of watering, frequency of watering, quantity of water required for livestock, water borne diseases, water treatments followed, water availability and farmers’s opinion on water quality. Most of the farmers used the same source of water for consumption to human and livestock. The contamination of water sources in the study area was mainly due to industrial effluents followed by, domestic sewage and agricultural waste. Water troughs were placed outside the shed by most of the farmers. Cleaning the water trough was practiced at weekly intervals by majority of the farmers. Aluminium vessels were used by most of the farmers for watering the livestock. Concentrates were mixed with water by most of the farmers for feeding the livestock. Majority of the farmers watered the cattle twice a day. Water treatment was not followed by most of the farmers. Water was available throughout the year as reported by almost all the farmers. However water quality monitoring has to be carried out to assess the quality of water sources available to livestock.